2019
DOI: 10.1021/acsami.9b17817
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Surface Chemistry and Structure in Highly Active Sputtered Pt3Y Catalyst Films for the Oxygen Reduction Reaction

Abstract: Platinum is the most widely used and best performing sole element for catalyzing the oxygen reduction reaction (ORR) in lowtemperature fuel cells. Although recyclable, there is a need to reduce the amount used in current fuel cells for their extensive uptake in society. Alloying platinum with rare-earth elements such as yttrium can provide an increase in activity of more than seven times, reducing the amount of platinum and the total amount of catalyst material required for the ORR. As yttrium is easily oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…For both samples (as‐deposited and after acid treatment) there are three contributions to the overall signal: bulk metallic yttrium (Y 0 ) around 155.9 eV (3d 5/2 ), yttrium oxide (Y 3+ ) around 158 eV , . There is a third peak that we assign to substochiometric Pt 3 Y oxide (Y–O) around 157 eV; where the material composition and oxidation is different to Y 2 O 3 , . There are notable trends with photon energy for all core levels.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…For both samples (as‐deposited and after acid treatment) there are three contributions to the overall signal: bulk metallic yttrium (Y 0 ) around 155.9 eV (3d 5/2 ), yttrium oxide (Y 3+ ) around 158 eV , . There is a third peak that we assign to substochiometric Pt 3 Y oxide (Y–O) around 157 eV; where the material composition and oxidation is different to Y 2 O 3 , . There are notable trends with photon energy for all core levels.…”
Section: Resultssupporting
confidence: 90%
“…There is no carbon present during the film deposition and as yttrium is so oxyphilic, the presence of a very small amount of oxygen in the chamber (during deposition, or from sputter cleaning) could cause substochiometric oxide to form. Previously, we have performed calculations based on this which have shown that subsurface oxygen (which we call substochiometric oxide) will have a shift towards slightly higher binding energies, the sputter cleaning presented in this paper provides further evidence of the existence of subsurface and substochiometric oxide . The percent content of Y 0 to Y–O, showing the distribution at different photon energies, can be found in the supplementary information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core of a PEMFC consists of the polymer electrolyte membrane sandwiched between two thin catalyst layers and two porous electrodes, which are called gas diffusion layers (GDLs). The catalyst layer has a great impact on the cost of fuel cells, and research efforts have been devoted to its improvement (Brown et al 2019). On the cathode catalyst layer surfaces, protons and oxygen participate in an exothermic chemical reaction the products of which are water and heat.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, it is a significantly challenging task to prepare alloy nanostructures for actual applications, mainly because yttrium has a very strong oxygen affinity to form Y 2 O 3 readily and the oxide is hardly reducible. 5 Therefore, most successful reports of Pt-Y nanoparticles have been made via a physical top-down approach, such as advanced sputtering techniques, 6,7 in which the nanoparticles were commonly prepared from the pure metals under a highly clean environment of oxygen-/moisture-tight conditions. 8 On the other hand, a more challenging chemical approach has recently been attempted ardently to obtain Pt-Y nanostructures because the approach has a more scalable potential.…”
mentioning
confidence: 99%